STATE POLICY TO COUNTER CRIME IN BORDER REGIONS IN A DIGITAL SOCIETY - Maya G. Dieva; Dureja Z. Zijadova (Russian Studies in Law and Politics)
Relevance. Crime in border regions poses the greatest danger to society and the state in the digital world. During the period of digitalization of society, the problem of criminal law risks with the use of information technology is becoming more dangerous, large-scale and intractable. As you know, the era of the dominance of digital technologies has not only positive consequences, opening up new opportunities for the development of society and the state, but also creates additional criminal threats to national security. In such circumstances, government policy is aimed at building an effective system of digital confrontation. In a digital society, the crime prevention system in the border regions of the Russian Federation, although based on the unified legal framework of state policy in the field of combating crime, cannot be the same for all regions of the country. Its construction should take into account regional economic, social, demographic, ethno-confessional, territorial, historical, cultural and national characteristics.